(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: This study aims to evaluate the treatment results of sudden deafness (SD) using hyperbaric oxygen therapy (HBOT). Subjects and methods: Prospective interventional study, comparing pre- and post-treatment results. Results: The study included participants with a mean age of 54.9 ± 15.1 years and a male-to-female ratio of 1.32. Among the patients, 43.1% did not report any factors associated with the disease. The majority of patients sought treatment within 7 days (64.6%). All patients (100%) presented with symptoms of hearing loss and tinnitus, and 95.1% experienced a feeling of fullness in the ear. The rising audiogram pattern was observed in 52.3% of cases. The cases with mild hearing loss represented the most prevalent proportion at admission (76.8%). After treatment, most patients achieved a normal pure-tone audiometry (PTA) result (63.8%); with only 1 patient classified as having moderate hearing loss. 50.7% of patients demonstrated complete improvement, while 14.5% showed partial improvement based on Siegel’s criteria. The HBOT-treated group exhibited a significantly greater improvement in PTA (18.9 ± 8.6dB) compared to the non-HBOT-treated group (12.9 ± 5.0dB) (p <0.05). Conclusion: Sudden deafness patients treated with HBOT exhibited better hearing recovery results than those treated with conventional medical interventions.